Finian's rainbow. - Lane, Burton, 1912-1997.; Canberra Philharmonic Society ([Canberra] : Canberra Philharmonic Society, 1981)
Poster advertising the Canberra Philharmonic Society's 1981 production of the musical "Finian's rainbow" at The Playhouse, Canberra Theatre, July 15-18. Features image of a cloud (in which the title appears) in front of a rainbow. Includes performance credits and booking details at the foot of the image. Rainbow stripes appear at both the head and foot of the poster.
Caption title.
Also available online
Keywords: Canberra Philharmonic Society -- Posters; Musicals -- Canberra -- Posters; Posters, Australian; Australia -- Posters; Australian